Landmarks and principal phases in the history of modern and contemporary Makedonia - Χασσιώτης, Ιωάννης Κ. (Παρατηρητής, 1992)
Landmarks and principal phases in the History of Makedonia under Ottoman rule -- Hellenic Makedonia since liberation: General observation and principal phases